2019
DOI: 10.1155/2019/9219847
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubular Development Is Impaired with Downregulation of MAPK/ERK Signaling, HIF-1α, and Catalase by Hyperoxia Exposure in Neonatal Rats

Abstract: Supplemental oxygen therapy (hyperoxia) is a widely used treatment for alveolar hypoxia in preterm infants. Despite being closely monitored, hyperoxia exposure is believed to undermine neonatal nephrogenesis and renal function caused by elevated oxidative stress. Previous studies have mostly focused on the hyperoxia-induced impairment of glomerular development, while the long-term impact of neonatal hyperoxia on tubular development and the regulatory component involved in this process remain to be clarified. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Mixed acute-and-chronic injury, where toxic exposures, disease states, and/or assessments were both acute (i.e., hours, days) and chronic (i.e., weeks, months, years) in the same study, were observed in human transplant rejection (biopsy 1 week to 3 years post-transplant) [ 88 ], swine hepatitis E virus infection (7 and 14 days post-inoculation) [ 52 ], CO 2 pneumoperitoneum-induced stress in hydronephrotic kidneys (2 weeks hydronephrosis, 2 days post-pneumoperitoneum) [ 53 ], mesangial proliferative glomerulonephritis induced by snake venom (1 to 14 days post-injection) [ 99 ], unilateral ureteral obstruction (1 to 14 days of obstruction) [ 100 ], uranyl acetate exposure (1 to 28 days of exposure) [ 101 ], aristocholic acid nephropathy (5 and 30-day daily exposure) [ 102 ], and neonatal hyperoxia (tested 1 to 60 postnatal days, exposed to hyperoxia first 14 days) [ 103 ]. Fourteen days after impact is a very common assessment time point for these kinds of kidney injuries [ 52 , 53 , 99 , 101 , 103 ]. In the majority of cases, TUNEL-positive cells were localized in tubules and collective ducts.…”
Section: Tunel Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed acute-and-chronic injury, where toxic exposures, disease states, and/or assessments were both acute (i.e., hours, days) and chronic (i.e., weeks, months, years) in the same study, were observed in human transplant rejection (biopsy 1 week to 3 years post-transplant) [ 88 ], swine hepatitis E virus infection (7 and 14 days post-inoculation) [ 52 ], CO 2 pneumoperitoneum-induced stress in hydronephrotic kidneys (2 weeks hydronephrosis, 2 days post-pneumoperitoneum) [ 53 ], mesangial proliferative glomerulonephritis induced by snake venom (1 to 14 days post-injection) [ 99 ], unilateral ureteral obstruction (1 to 14 days of obstruction) [ 100 ], uranyl acetate exposure (1 to 28 days of exposure) [ 101 ], aristocholic acid nephropathy (5 and 30-day daily exposure) [ 102 ], and neonatal hyperoxia (tested 1 to 60 postnatal days, exposed to hyperoxia first 14 days) [ 103 ]. Fourteen days after impact is a very common assessment time point for these kinds of kidney injuries [ 52 , 53 , 99 , 101 , 103 ]. In the majority of cases, TUNEL-positive cells were localized in tubules and collective ducts.…”
Section: Tunel Applicationsmentioning
confidence: 99%
“…Inflammation was identified by IHC of tumor necrosis factor alpha (TNFα) [ 134 ]; tumor growth factors TGFβ [ 66 ] and TGF-β1 [ 135 ]; serine/threonine kinase 1 (SGK1) [ 135 ]; electron-transfer flavoprotein, beta-subunit (ETFβ) [ 136 ]; Janus kinase-2 (JAK2) [ 137 ]; signal transducer and activator of transcription 3 (STAT3) [ 137 ]; nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB) [ 137 ] and its inhibitor protein IκB [ 137 ]. For kidney injury assessment, kidney injury molecule-1 (KIM-1) [ 24 ], aquaporin-1 channel (AQP-1) [ 45 ], hypoxia-inducible factor 1-alpha transcription factor (HIF-1α) [ 103 ], Asc-type amino acid transporter-1 (Asc-1) [ 121 ], mammalian target of rapamycin (mTOR) [ 131 ] kinase, and transglutaminase II [ 89 ] were used. Oxidative kidney injury was studied using markers such as 8-hydroxyguanosine (8OHdG) [ 102 ], neutrophil gelatinase-associated lipocalin (NGAL) [ 102 ], NAD-dependent deacetylase sirtuin-1 (SIRT1) [ 138 ], and heme oxygenase 1 (HO-1) [ 90 ].…”
Section: Tunel Quantification and Colocalization Techniquesmentioning
confidence: 99%
“…However, currently, the effects of HIF and vascular endothelial growth factor (VEGF) are not well known. Some studies on renal diseases found that HIF-1α played a protective role [13][14][15], but others reported that it was a risk factor [16][17][18]. Current evidence indicated that HIF-1α could be regulated by some NR [19][20][21]; however, there was no report showing the relationship between NCOAs and HIF-1α.…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental oxygen therapy (hyperoxia) is commonly administered in the management of premature infants with respiratory disorders [ 1 , 2 ]. Nonetheless, increasing evidence from various clinical and experimental observations suggests that neonatal hyperoxia may cause oxidative damage and adversely affects glomerular and tubular maturity [ 3 , 4 ]. These adverse effects are manifested by enlarged renal corpuscles, renal tubular injuries, and interstitial inflammation during the perinatal period, which might extend into adulthood and influence renal function [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%